Synthesis, characterization and photoluminescence of Dy3+-doped MgZnO nanophosphors - Rajput P.; Vashishtha P.; Gupta G.; Singh P.; Pathania K. (My University, 2025)
MgZnO and MgZnO: Dy3+ (x = 0.0025–0.025) nanoparticles were synthesized by the combustion method. The as-synthesized samples were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), UV–visible spectroscopy (UV–Vis) and photoluminescence (PL) techniques. XRD studies confirmed the presence of wurtzite hexagonal structure of all the samples with the crystallite size in the range of 30–50 nm range. The XRD results were also in good agreement with the TEM results. The EDS spectra confirmed the presence of all the elements in the samples prepared. UV–Vis measurements indicated variation in bandgap values with increasing doping concentration. PL spectrum showed enhanced blue emission and tunability of blue emission could be observed with variation in dopant concentration. Excellent emission intensity of the phosphor was suitable for application in display devices. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.